2008
DOI: 10.1515/jaots-2008-0106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zinc Oxide-Based Photocatalytic Degradation of a Commercial Pesticide

Abstract: In this study, the performance of zinc oxide as a catalyst for photodegradation of commercial herbicide 2,4-D AMINA 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For chlorpyrifos degradation Kanmoni et al [42] used ZnO concentrations between 0.1 g/L and 1 g/L and showed that the best results were at a ZnO dosage of 0.75 g/L. Burbano et al [43] quantified the elimination of dimethylamine salt of 2,4-dichlorophenoxyacetic acid by photodegradation and reported as appropriate a zinc oxide concentration of 0.35 g/L. Ceretta et al [44] coupled the bacteria effect with that of a composite containing ZnO and polypyrrole and concluded that the adequate catalyst dosage for Direct Black azo dye degradation was of 2 g/L.…”
Section: Influence Of Photocatalyst Concentrationmentioning
confidence: 99%
“…For chlorpyrifos degradation Kanmoni et al [42] used ZnO concentrations between 0.1 g/L and 1 g/L and showed that the best results were at a ZnO dosage of 0.75 g/L. Burbano et al [43] quantified the elimination of dimethylamine salt of 2,4-dichlorophenoxyacetic acid by photodegradation and reported as appropriate a zinc oxide concentration of 0.35 g/L. Ceretta et al [44] coupled the bacteria effect with that of a composite containing ZnO and polypyrrole and concluded that the adequate catalyst dosage for Direct Black azo dye degradation was of 2 g/L.…”
Section: Influence Of Photocatalyst Concentrationmentioning
confidence: 99%
“…It is also possible to find such pollutants in surface water and groundwater, which also require treatment to achieve an acceptable quality of drinking water (Zhang et al, 1994;Ahmed et al, 2011). In the field of pollutant degradation, photocatalysis is gaining considerable attention (Anandan et al, 2007;Burbano et al, 2008;Blinova et al, 2010). In the last two decades, to encourage specific redox processes on semiconductor surfaces, the use of colloidal semiconductors and the introduction of catalysts have been adopted (Daneshvar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The GAOX group (Universidad del Valle, 2008) published a study in which they evaluated the artificial UV‐assisted photocatalytic discoloration of methylene blue (MB) with a CPC and a tubular photoreactors. The MB removal were 70.8 % for the CPC and 63.46 % for the tubular photoreactor, respectively [34] …”
Section: A Review Of the Aops Past In Colombiamentioning
confidence: 96%
“…The MB removal were 70.8 % for the CPC and 63.46 % for the tubular photoreactor, respectively. [34] The Research Group on Applied Physicochemical Processes (Universidad de Antioquia, 2008) evaluated the photocatalytic degradation of a real wastewater from a chemical industry using a solar photoreactor of flat plates with TiO 2 /SiO 2 coating. They obtained a COD removal from 6 to 46 % and good biodegradability indexes, which proved that photocatalysis is a feasible technology to be coupled with biological processes.…”
Section: A Review Of the Aops Past In Colombiamentioning
confidence: 99%